The Mast Cell, Contact, and Coagulation System Connection in Anaphylaxis - Guilarte, Mar; Sala-Cunill, Anna; Luengo, Olga; Labrador-Horrillo, Moisés; Cardona, Victoria (Frontiers in Immunology, 2017)
Anaphylaxis is the most severe form of allergic reaction, resulting from the effect of mediators and chemotactic substances released by activated cells. Mast cells and basophils are considered key players in IgE-mediated human anaphylaxis. Beyond IgE-mediated activation of mast cells/basophils, further mechanisms are involved in the occurrence of anaphylaxis. New insights into the potential relevance of pathways other than mast cell and basophil degranulation have been unraveled, such as the activation of the contact and the coagulation systems. Mast cell heparin released upon activation provides negatively charged surfaces for factor XII binding and auto-activation. Activated factor XII, the initiating serine protease in both the contact and the intrinsic coagulation system, activates factor XI and prekallikrein respectively. Factor XII-mediated bradykinin formation has been proven in the human plasma of anaphylactic patients as well as in experimental models of anaphylaxis. Moreover, the severity of anaphylaxis is correlated with the increase in plasma heparin, bradykinin formation and the intensity of contact system activation. Factor XII also activates plasminogen in the fibrinolysis system. Mast cell tryptase has been shown to participate in fibrinolysis through plasmin activation and by facilitating the degradation of fibrinogen. Some usual clinical manifestations in anaphylaxis, such as angioedema or hypotension, or other less common, such as metrorrhagia, may be explained by the direct effect of the activation of the coagulation and contact system driven by mast cell mediators.